Relevance of Gender Justice Values in PAI Learning Towards The Formation of Students' Social Awareness - Abas, Siti Zulaiha; Kasim Yahiji; Baso Tola; Zohra Yasin (Pascasarjana IAIN Sultan Amai Gorontalo, 2025)
This article aims to theoretically explore the impact of Islamic Religious Education (PAI) learning, with a focus on gender justice, on students' social awareness through a library research approach. This study involves analyzing relevant literature, including books, scientific journals, policy documents, and previous research on gender justice in Islamic education and the development of social awareness. The results of the study show that PAI learning that incorporates gender justice values can significantly enhance students' social awareness. This is because gender justice in education promotes an equal mindset, respects differences, and encourages active participation in social life. Therefore, integrating gender justice into the curriculum and PAI teaching process is a crucial step in building an inclusive civil society.